Panca Jiwa Pondok Pesantren: Sebuah Analisis Kritis - Ummah, Fiena Saadatul (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2017)
The five souls of pondok pesantren are not only considered as a provision that must be possessed, but must be imbued and applied through habits in the life of pondok pesantren. In other words, the souls of the pesantren are not merely used as slogans or theories, but actually carried out in the form of traditions or sunnahs that run every day at the boarding school. An atmosphere of life that is Islamic, tarbawi, and ma'hadi which is full of values of struggle and sacrifice, even with a life that is encompassed by a spirit of sincerity, a spirit of simplicity, a spirit of independence, a spirit of ukhuwah Islamiyah and a spirit of responsibility that is responsible for a witness and can see an atmosphere that can be felt directly in daily life at the pesantren.